Efeito do período de envelhecimento acelerado no teste de condutividade elétrica e na qualidade fisiológica de sementes de feijão - da Silva Binotti, Flavio Ferreira [UNESP]; Haga, Kuniko Iwamoto [UNESP]; Cardoso, Eliana Duarte [UNESP]; Alves, Charline Zaratin [UNESP]; de Sa, Marco Eustaquio [UNESP]; Arf, Orivaldo [UNESP] (Universidade Estadual de Maringá (UEM), Pro-reitoria Pesquisa Pos-graduacao, 2008)
The high quality of seed trading for producers is very important to obtain high productivity. The aim of this work was to evaluate the effects of different periods of artificial seed aging on contents of sugars, proteins, amino acids and ions, on imbibition solution of electrical conductivity test, as well as its relationships with standard germination and vigor in bean seeds at the Perola cultivar. The research was carried out at the Laboratory of Seed Analysis - Faculdade de Engenharia - Unesp - Campus de Ilha Solteira. The experimental design was in completely randomized blocks. The seeds were submitted to eight accelerated aging conditions (zero, 24, 48, 72, 96, 120, 144 and 168 hours). The seed germination, seed vigor and leakage contents in exudates of bulk conductivity were Influenced by the increase in the time of seed exposition to accelerated aging. After seventy-two hours of exposition to the aging, a considerable decline in seed germination and vigor was observed. There was also an increase of leakage contents, such as amino acids, sugars, potassium and phosphorus ions. The increase of leakage contents is inversely related to seeds germination and vigor.
Relationships of acellerated aging time with bulk conductivity test and with physiological seed quality in common bean
Keywords: Phaseolus vulgaris L.; leakage; protein; ions; seed germination; vigor